2023
DOI: 10.1111/pbi.14025
|View full text |Cite
|
Sign up to set email alerts
|

TaTPP‐7A positively feedback regulates grain filling and wheat grain yield through T6P‐SnRK1 signalling pathway and sugar–ABA interaction

Abstract: Summary Grain size and filling are two key determinants of grain thousand‐kernel weight (TKW) and crop yield, therefore they have undergone strong selection since cereal was domesticated. Genetic dissection of the two traits will improve yield potential in crops. A quantitative trait locus significantly associated with wheat grain TKW was detected on chromosome 7AS flanked by a simple sequence repeat marker of Wmc17 in Chinese wheat 262 mini‐core collection by genome‐wide association study. Combined with the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 77 publications
1
12
0
Order By: Relevance
“…However, it is worth noting that the expression of OsTPP1 and OsTPP3 was reduced in inferior grains of the aba8ox2 mutant, an ABA catabolism gene, resulting in an elevated T6P level and thus promoting grain filling [ 56 ], indicating that an elevated ABA content might not always increase the expression of OsTPP3 in different tissues of rice. In addition, the overexpression of TaTPP - 7A promoted the grain filling of wheat kernels and induced the expression of genes involved in the ABA signaling pathway [ 57 ]. In Arabidopsis , the expression of the ABI4 gene, which encodes a key component of the ABA signaling pathway, is regulated by the AtTPS1 gene [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, it is worth noting that the expression of OsTPP1 and OsTPP3 was reduced in inferior grains of the aba8ox2 mutant, an ABA catabolism gene, resulting in an elevated T6P level and thus promoting grain filling [ 56 ], indicating that an elevated ABA content might not always increase the expression of OsTPP3 in different tissues of rice. In addition, the overexpression of TaTPP - 7A promoted the grain filling of wheat kernels and induced the expression of genes involved in the ABA signaling pathway [ 57 ]. In Arabidopsis , the expression of the ABI4 gene, which encodes a key component of the ABA signaling pathway, is regulated by the AtTPS1 gene [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…The G-to-A mutation at position 1,049 of the HMGS-7A coding region leads to amino acid change from glycine (Gly) to aspartic acid (Asp). In previous studies, several genes related to grain size and weight have been mapped and cloned on wheat chromosome 7A, including TaTPP-7A (7A, 135.0 Mb; Liu et al., 2023 ), TaGASR7 (7A, 176.0 Mb; Zhang et al., 2015 ), TaTGW-7A (7A, 211.6 Mb; Hu et al., 2016 ), TaGW8 (7A, 257.3 Mb; Yan et al., 2019 ), and TaIAA21 (7A, 488.5 Mb; Jia M et al, 2021 ). The TraesCS7A03G0625900 ( HMGS-7A ) gene identified in this study does not overlap with these reported grain morphology genes.…”
Section: Discussionmentioning
confidence: 99%
“…For example, overexpression of OsTPP1 in rice promotes seed germination and increases rice yield and stress resistance [ 43 ]. In wheat, TaTPP7 promotes seed grain filling [ 44 ]. However, whether the changes of RhTPS / TPP genes in roses are caused by stress environments or due to different metabolic patterns compared to other plants still needs to be further studied through experiments.…”
Section: Discussionmentioning
confidence: 99%